Bridging the gap: strategies for recognizing and managing post-COVID conditions - Khan, Muhammad H.; Becker, Richard C. (Frontiers in Medicine, 2024)
Post-COVID conditions (PCC), pose significant challenges for healthcare providers, employers, community leaders, and patients because of their wide-ranging, fluctuating, or persisting symptoms without well-established diagnostic tests to secure a diagnosis. Estimates suggest that up to 20–30% of adults recovering from COVID-19 develop PCC, potentially affecting millions or tens of millions of people in the United States alone. The ongoing endemic coupled with the prevalence of PCC underscores an urgent need for awareness and an understanding of potentially associated conditions, long-term management strategies, and cost-effective screening approaches for cardiovascular health. Individuals experiencing PCC present with a wide array of symptoms. Prevalence of chronic conditions such as post-infectious pulmonary fibrosis, cardiomyopathy, and accelerated coronary artery, cerebrovascular, and peripheral vascular disease further emphasizes the need for community-wide policies and practices. Screening for PCC is recommended, particularly among high-risk individuals, including those with comorbid conditions and exposure to specific SARS-CoV-2 variants, to facilitate early diagnosis, counseling, targeted interventions, and improved quality of life. The aim of this review is to highlight the urgent need for awareness, understanding and management of PCC, focusing on development of screening strategies and targeted interventions to help facilitate early diagnosis and enhance the quality of life for affected individuals. In our view early detection and management of PCC not only improves the quality of life but also improves psychosocial health. Patient-centered approaches, standardized screening tools, and initiatives aimed at enhancing understanding and treatment options, such as the RECOVER and N3C programs, are essential for effective management of PCC.